Microbiota composition and distribution along the female reproductive tract of women with endometriosis - Weixia Wei; Xiaowei Zhang; Huiru Tang; Liping Zeng; Ruifang Wu (BMC, 2020)
Abstract Endometriosis (EMS) is a multifactorial disease that affects 10%-15% women of reproductive age and is associated with chronic pelvic pain and infertility. The pathogenesis of EMS has not been consistently explained until now. In this study, we involved 36 endometriosis patients and 14 control subjects who performed laparoscopic surgery due to gynecological benign tumor. The samples from lower third of vagina (CL), posterior vaginal fornix (CU), cervical mucus (CV), endometrium (ET) and peritoneal fluid (PF), were collected and sequenced by 16S rRNA amplicon. The continuous change of the microbiota distribution was identified along the reproductive tract. The flora in lower reproductive tract (CL, CU) were dominated by Lactobacillus. Significant difference of the community diversity began showing in the CV of EMS patients and gradually increased upward the reproductive tract. It indicates the microbiota in cervical samples is expected to be an indicator for the risk of EMS. This study also highlights the decreasing of Lactobacillus in vaginal flora and the increasing of signature Operational Taxonomic Units (OTUs) in transaction zone (CV) and upper reproductive tract (ET, PF) of EMS patients, which reflect the alteration of microbial community associated with EMS, participation of specific colonized bacteria in the EMS pathogenesis and relationship between microbiota and development of disease.